2016
DOI: 10.1097/ijg.0000000000000493
|View full text |Cite
|
Sign up to set email alerts
|

Trabeculectomy and Combined Phacoemulsification-Trabeculectomy: Outcomes and Risk Factors for Failure in Primary Angle Closure Glaucoma

Abstract: Purpose To evaluate tonometric outcomes of patients with primary angle closure glaucoma (PACG) who have undergone trabeculectomy with mitomycin C (MMC) with and without concurrent phacoemulsification and to identify risk factors for post-operative failure. Patients and Methods Retrospective cohort study of 44 eyes of 33 phakic patients who underwent trabeculectomy with MMC with or without combined phacoemulsification for PACG. The primary endpoint was qualified tonometric success at 12 months according to pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 22 publications
3
21
0
Order By: Relevance
“…At both time points, patients having received trabeculectomy had a significantly higher IOP reduction compared to patients after XEN gelstent implantation. The changes in IOP after both procedures are similar to reported IOP changes in current literature [20][21][22][23][24]. Gedde et al reported a mean IOP reduction of 12.9 mmHg one year after trabeculectomy, which is slightly higher than the reduction 10.5 mmHg we observed but within the standard deviation range [23].…”
Section: Plos Onesupporting
confidence: 89%
“…At both time points, patients having received trabeculectomy had a significantly higher IOP reduction compared to patients after XEN gelstent implantation. The changes in IOP after both procedures are similar to reported IOP changes in current literature [20][21][22][23][24]. Gedde et al reported a mean IOP reduction of 12.9 mmHg one year after trabeculectomy, which is slightly higher than the reduction 10.5 mmHg we observed but within the standard deviation range [23].…”
Section: Plos Onesupporting
confidence: 89%
“…Similarly, the mean number of IOP-lowering medications used at 24 months was not statistically significantly different between treatment groups [30], suggesting limited long-term effectiveness of the device. We did not expect to see additional IOP lowering in the phaco + implant group, because many studies looking at trabeculectomy and phaco-trabeculectomy have shown comparable IOP lowering with both procedures [31][32][33][34][35][36][37][38]. Both phacoemulsification and trabeculectomy techniques have evolved, which might explain why more recent papers report no differences in outcomes between trabeculectomy alone vs combined with phacoemulsification.…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, trabeculectomy and aqueous tube shunts have been the primary approaches for patients with moderate to severe CACG with poorly controlled IOP. [1213] While trabeculectomies and tubes have been shown to significantly lower IOP, they are associated with significant complications. [12] The rate of reoperation in the Tube Versus Trabeculectomy (TVT) study was 9% in the tube group and 29% in the trabeculectomy group at 5 years.…”
Section: Discussionmentioning
confidence: 99%
“…[1213] While trabeculectomies and tubes have been shown to significantly lower IOP, they are associated with significant complications. [12] The rate of reoperation in the Tube Versus Trabeculectomy (TVT) study was 9% in the tube group and 29% in the trabeculectomy group at 5 years. [14] These incisional surgeries can result in failure due to scarring, decreased quality of life due to bleb-related foreign body sensation, induced astigmatism, and secondary cataracts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation